Coprophagous Hydrophilid Beetles (Coleoptera, Hydrophilidae, Sphaeridiinae) Distribution in the Polish Carpathians - Czesław Greń (Insects, 2020)
Research on coprophagous beetles of the Hydrophilidae family in the Polish Carpathians was conducted from 2011 to 2013. The beetles were caught using baited traps. The research sites were selected to take into account both the horizontal diversity of habitat conditions and the vertical diversity associated with elevation above sea level. During the study, 9589 coprophagous hydrophilid individuals were collected, representing 17 species and five genera. Two species that were new to Poland were found: Cercyon tatricus and Pachysternum capense. The vertical ranges of the individual species of coprophagous hydrophilid beetles within the Polish Carpathians were determined as well as the elevations above sea level, with the highest and lowest species richness of this group of insects. The capture of Pachysternum capense in the Tatra Mountains may indicate the existence of an unrecognized path of migration of small insects from Southern to Northern Europe. The route and mechanisms of their migration are discussed.